Pembatalan Akta Hibah Akibat Perbuatan Melawan Hukum dan Bertentangan dengan Hukum Waris: Studi Putusan Nomor 85/Pdt.G/2021/PN Bdg - Amelia, Helda; Abdullah, Zaitun; Wuryandari, R. Utji Sri Wulan (SIGn Jurnal Hukum, 2025)
The annulment of Grant Deeds due to unlawful acts by the Grantee within the context of an inheritance dispute raises complex legal issues concerning the conflict between the formality of deeds and the protection of free will. This research aims to analyze the basis of the Panel of Judges’ reasoning in finding unlawful acts by the child (Grantee) and annulling the Grant Deeds, as well as to analyze the forms of legal protection afforded to the Grantor in Decision Number 85/Pdt.G/2021/PN Bdg. The research method employed is normative legal research utilizing case study, statute, and conceptual approaches, with a qualitative descriptive-analytical analysis of the aforementioned decision. The analysis results indicate that the Panel of Judges annulled the Grant Deeds based on the non-fulfillment of the subjective requirement for a valid agreement according to Article 1320 of the Civil Code, namely the absence of free consent resulting from defects of consent (duress and abuse of circumstances) caused by the proven unlawful acts of the Defendant. The conflict between the grant mechanism and the principles of joint marital property according to Law Number 1 of 1974 and the rules of inheritance law further reinforced the basis for annulment. The manifestation of legal protection for the Plaintiff was effectively realized through the annulment of the deeds, which restored the autonomy of will, the order for restitution for the recovery of material losses, the affirmation of correct inheritance rights providing legal certainty, and the judicial declaration of unlawful act as a form of juridical recognition of the violation of the rights. This decision underscores the court’s priority on substantive justice and the protection of aggrieved parties in family grant disputes tainted by unlawful acts.